REPORTS OF THE USE OF URTICACEAE COLLECTED IN BRAZIL AND DEPOSITED IN THE HERBARIA OF KEW (K), NEW YORK (NY) AND PARIS (P) - Corrado, Amanda Roberta [UNESP]; Gaglioti, Andre Luiz [UNESP]; Romaniuc Neto, Sergio; Ming, Lin Chau [UNESP] (Univ Estadual Paraiba, Editora-eduep, 2015)
information on species of Urticaceae Juss. The study approached the collections of exsiccates belonging to herbaria of the Royal Botanic Gardens (K), Kew, England; Museum National d'Histoire Naturelle (P), Paris, France; and New York Botanical Garden (NY), New York, USA, also printed sources and manuscripts. We analyzed more than 2800 exsiccates, comprising the period between 1783 and 2003. From the information labels of the exsiccates, it was possible to obtain the use and common name of the Urticaceae species. A total of thirteen species with register of use were find in the labels, six genera of Urticaceae: five species of Pourouma Aubl., three of Cecropia Loefl., two of Urera Gaudich., one of Boehmeria Jacq., one of Coussapoa Aubl., one of Laportea Gaudich. Five categories of usage were identify: (1) animal feeding; (2) human feeding; (3) medicinal; (4) fiber and (5) fuel. The analysis of the labels registers pointed to be efficient to raise information related to Urticaceae species, and combined to the research of printed sources and manuscripts provide more details to the data. Furthermore, adding information to the review of the collections history in Brazil. It is necessary to establish initiatives which facilitate the access to documents associated to exsiccates, like the manuscripts of collectors, for continuing the advances in the retrieval of knowledge registered.
Keywords: Historical ethnobotany; Exsiccates; Historical collections; Useful plants